IDE DIVERSI DALAM TINDAK PIDANA RINGAN YANG DILAKUKAN ORANG DEWASA BERBASIS KEADILAN - Riya Novita (Jurnal Pembaharuan Hukum, 2015)
Indonesia's legal system which applies to offenders focuses on punishment as the penalty. Kajahatan perpetrators will be punished so that security and order within the communitycan be restored sehigga impressed penalty is revenge on the perpetrators of crime victims. But the punishment will never improve the state of society, because it does not deter criminalsfrom committing a similar crime or even a more heinous, also ignoring the losses suffered by victims. The researchers' goal here, to put the idea of diversion is the transfer of criminal casesoutside the criminal justice process. This type of research is the description of the analysis is to do research that will be devotedto seek or find the data needed to answer the problem. The results of this study are known to retributive punishment does not guarantee reduced crime. It is based on the data presented Writer, convictions resulted in the over-capacity prison.By applying a misdemeanor diversion in the task of law enforcement to be reduced, budget handling criminal offensescan be diverted to handling criminal offense heavier and their diversion agreement then the victim is much more attention.